محددات تطبيق الإدارة الإستراتيجية في المؤسسات الجزائرية "دراسة ميدانية لعينة من المؤسسات في ولاية الوادي" - اسماعيل عبد اللاوي; أيوب محمدي; عبد الخالق صالحي; محمد مفتاح (جامعة الوادي university of eloued, 2024)
"ملخص تحاول هذه الدراسة إلى توضيح أهم المحددات لتطبيق الإدارة الاستراتيجية في المؤسسات الجزائرية، حيث تتناول الدراسة عوامل متعددة منها البيئة التنظيمية الداخلية مثل الهيكل التنظيمي والثقافة المؤسسية السائدة، وكذلك العوامل الخارجية كالممارسات السياسية والتغيرات الاقتصادية والاجتماعية. كما سلطنا الضوء على أهمية القيادة الفعالة والتخطيط الاستراتيجي الشامل وتوافر الموارد البشرية والمالية المؤهلة. وللتعرف على مدى تطبيق الإدارة الإستراتيجية في المؤسسات الجزائرية فقد اعتمدنا في دراستنا على الأسلوب التحليلي الوصفي، فقمنا بأخذ عينات لعدد من المؤسسات الخاصة والعامة في ولاية الوادي، باستخدامنا لأسلوب الاستبانة وذلك بالتقرب من دائرة أصحاب القرار في هاته المؤسسات لكشف مدى تطبيقها للإدارة الإستراتيجية. أظهرت نتائج الدراسة على أن الإدارة العليا بالمؤسسات الجزائرية سواء كانت عامة أو خاصة، هي صاحبة القرار، وأن نجاح الإدارة الإستراتيجية وتطبيقها في المؤسسات الجزائرية يتمثل في القيادة الفعالة والرشيدة لهاته المؤسسات. وخلصنا في نهاية الدراية لأهم التوصيات العملية المقترحة من أجل تحسين المؤسسات من أدائها وتحقيق أهدافها المرجوة ومن أهمها: تعزيز التعليم والتدريب، تطوير ثقافة مؤسسية داعمة، استخدام التكنولوجيا الحديثة، تحديد الأهداف الإستراتيجية بوضوح، تحسين عمليات التقييم والمراقبة، تعزيز الشفافية والمساءلة، الاستفادة من الخبرات العالمية." "Abstract This study aims to elucidate the main determinants of the application of strategic management in Algerian institutions. The study addresses various factors, including internal organizational environment such as organizational structure and prevailing institutional culture, as well as external factors such as political practices and economic and social changes. We also highlighted the importance of effective leadership, comprehensive strategic planning, and the availability of qualified human and financial resources. To understand the extent of strategic management application in Algerian institutions, our study relied on a descriptive analytical method. We sampled several public and private institutions in the Wilaya of El Oued, using a questionnaire approach by engaging with decision-makers within these institutions to uncover the extent of their strategic management implementation. The study's results indicate that the senior management of Algerian institutions, whether public or private, holds the decision-making power, and the success of strategic management implementation in these institutions is manifested through effective and prudent leadership. In conclusion, the study offers practical recommendations to improve institutional performance and achieve desired objectives. These include enhancing education and training, developing a supportive institutional culture, utilizing modern technology, clearly defining strategic goals, improving evaluation and monitoring processes, reinforcing transparency and accountability, and leveraging global expertise."
Keywords: إستراتيجية، تخطيط إستراتيجي، إدارة إستراتيجية، تحليل إستراتيجي، بيئة داخلية، بيئة خارجية، ثقافة تنظيمية، هيكل التنظيمي. الترميز الاقتصادي (JEL): P11 Strategy; Strategic Planning; Strategic Management; Strategic Analysis; Internal Environment; External Environment; Organizational Culture; Organizational Structure. Economic Classification (JEL): P11